Analyzing the Influence of Brand Image, Product Quality, and Price on Consumer Purchase Choices: Menganalisis Dampak Citra Merek, Kualitas Produk, dan Harga terhadap Keputusan Pembelian Konsumen: Studi Kuantitatif - Fachrur Rozi; Dewi Komala Sari (Academia Open, 2022)
This research aims to investigate the influence of brand image, product quality, and price on consumer purchasing decisions in the context of Bolu Malang Singosari in Singosari. A quantitative approach was employed, utilizing a sample of 100 consumers as respondents. The sampling technique employed the Lemeshow formula due to the unknown or infinite total population. The data analysis involved conducting classical assumption tests and multiple linear regression analysis, with data processed using SPSS 25 for Windows. The findings of this study provide evidence that brand image, product quality, and price individually impact purchasing decisions at Bolu Malang Singosari. Moreover, the results reveal that these factors collectively exert a significant influence on consumer purchasing decisions. The implications of these findings highlight the significance of brand image, product quality, and price in shaping consumer behavior, emphasizing the need for businesses to strategically manage these factors to enhance their competitiveness and attract customers. Highlights: Brand image significantly influences purchasing decisions: The study establishes a strong impact of brand image on consumer purchasing decisions, highlighting the importance of effective brand management strategies. Product quality plays a crucial role in consumer decision-making: The research reveals that consumers consider product quality as a vital factor when making purchasing decisions, emphasizing the need for businesses to focus on delivering high-quality products. Price has a significant effect on consumer behavior: The study highlights the influence of price on consumer purchasing decisions, indicating the necessity for businesses to adopt appropriate pricing strategies to attract and retain customers. Keywords: Brand image, Product quality, Price, Consumer purchasing decisions, Quantitative study